Monitoring Food Waste Levels in Gulf Cooperation Council (GCC) Countries: A Country Comparison - Alsheyadi, Said Juma; Bathmanathan, Vathana A.P. (Current Nutrition & Food Science, 2025)
IntroductionFood waste has become a global concern due to its negative impacts on the environment, economy and society.ObjectiveTo address this issue, the United Nations Sustainable Development Agenda aims to reduce food waste by 50% by the year 2030. However, monitoring progress towards this goal in GCC countries has been challenging due to the lack of accurate data on food waste.MethodsThe research used a comparative study methodology that focuses on a regional level analysis utilizing a data set of Food Waste Index (FWI).ResultsBy using cross-country comparative analysis as a methodology, this research article offers a solution to this problem by presenting a model for comparative statistical analysis that can reduce uncertainty in food waste data.ConclusionThe article highlights the importance of integrating the Food Waste Index databases with the Global Food Security Index databases to bridge the data gap and effectively monitor efforts to reduce food waste.
Keywords: Food waste